Compact world atlas - Mumford, Simon (DK/ Penguin Random House, 2023)
"If you're interested in finding out more about the geography of the world we live in, then this world atlas book is perfect for you. Compact World Atlas provides an excellent source of accurate and informative geographical information in an attractive, affordable, user-friendly package"--